2013
DOI: 10.5603/fm.2013.0003
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of three-dimensional reconstruction of the human osseous labyrinth from micro-computed tomography scans

Abstract: The adult human temporal bone was investigated using micro-computed tomography scans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Such anomalous bony obstructions can interfere with transcutaneous needle placement into the foramen ovale and distort anatomic relationships during approaches to the cranial base. [4,6,7,[10][11][12][13][14][15][16] According to a CT analysis of infratemporal fossa anatomical variants, cannulation of the foramen ovale accompanied by a pterygoalar bar may be impossible using the Hartel approach. [9] A more detailed study suggested that in rare cases, the width of the foramen ovale was approximately 1 mm and that cannulation with the 14-gauge cannula (2.108-mm diameter) used for balloon rhizotomy would be impossible in a subset of these foramina for 2 reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such anomalous bony obstructions can interfere with transcutaneous needle placement into the foramen ovale and distort anatomic relationships during approaches to the cranial base. [4,6,7,[10][11][12][13][14][15][16] According to a CT analysis of infratemporal fossa anatomical variants, cannulation of the foramen ovale accompanied by a pterygoalar bar may be impossible using the Hartel approach. [9] A more detailed study suggested that in rare cases, the width of the foramen ovale was approximately 1 mm and that cannulation with the 14-gauge cannula (2.108-mm diameter) used for balloon rhizotomy would be impossible in a subset of these foramina for 2 reasons.…”
Section: Discussionmentioning
confidence: 99%
“…[4,5] When the pterygoalar ligament forms a large bone bar lateral to the foramen ovale, it can obliterate the lumen of the foramen ovale and block the passage of a needle aimed at the foramen ovale using the Hartel approach. [4][5][6][7] In an examination of dried skulls, Elnashar et al [8] found that all pterygoalar bars causing complete or near-complete obliteration of the lumen would theoretically disturb needle access to the foramen ovale using the Hartel approach and that the presence of pterygoalar ossification could directly influence the choice of the most Both patients provided written informed consent for the publication of their case report.…”
Section: Introductionmentioning
confidence: 99%